Hierarchical Sandwich-Like Structure of Ultrafine N-Rich Porous Carbon Nanospheres Grown on Graphene Sheets as Superior Lithium-Ion Battery Anodes - Xie, Zhiqiang (2017)
A sandwich-like, graphene-based porous nitrogen-doped carbon (PNCs@Gr) has been prepared through facile pyrolysis of zeolitic imidazolate framework nanoparticles in situ grown on graphene oxide (GO) (ZIF-8@GO). Such sandwich-like nanostructure can be used as anode material in lithium ion batteries, exhibiting remarkable capacities, outstanding rate capability, and cycling performances that are some of the best results among carbonaceous electrode materials and exceed most metal oxide-based anode materials derived from metal orgainc frameworks (MOFs). Apart from a high initial capacity of 1378 mAh g–1 at 100 mA g–1, this PNCs@Gr electrode can be cycled at high specific currents of 500 and 1000 mA g–1 with very stable reversible capacities of 1070 and 948 mAh g–1 to 100 and 200 cycles, respectively. At a higher specific current of 5000 mA g–1, the electrode still delivers a reversible capacity of over 530 mAh g–1 after 400 cycles, showing a capacity retention of as high as 84.4%. Such an impressive electrochemical performance is ascribed to the ideal combination of hierarchically porous structure, a highly conductive graphene platform, and high-level nitrogen doping in the sandwich-like PNCs@Gr electrode obtained via in situ synthesis.